The theory of advanced multi-layer thin film heat transfer gauges - Doorly, J; Oldfield, M (Pergamon Journals Ltd., 1987)
This paper describes the theory of a transient method of measuring heat transfer rate to metal substrates coated with an electrical insulator, using thin film resistance thermometers. This builds on the already well-established system which uses semi-infinite insulating substrates. It is intended that the new technique will have application in rotating turbine test rigs, since there is at present a lack of suitable instrumentation which can be easily manufactured, and which does not interfere with the flow. The new system described here shows that multi-layer substrate gauges can be used. This paper presents analyses of layered gauges and gives sample predictions and calibrations.